Mangrove vegetation analysis in Bama beach Baluran National Park - Sasea, Louis Ivana; Sueb, Sueb; Ibrohim, Ibrohim (Univeritas Papua, 2022)
Research was conducted on the analysis of mangrove vegetation on the coast of Bama, the Baluran National Park Situbondo Regency, in February 2021. The purpose of this study was to identify mangrove vegetation on Bama beach. Mangrove sampling is done purposive sampling by making plots on transect lines intermittently. Sizes 20 x 20 m2 for trees, 10 x 10 m2 for poles, 5 x 5 m2 for stake and 2 x 2 m2 for seedlings. Each plot identified the type and measured the diameter of the trunk and the number of individual mangroves. Important value index (IVI) is obtained by calculating species density, relative density, type frequency, relative frequency, type dominance, and relative dominance. The results showed that on the coast of Bama Baluran National Park, there are four types of mangroves, namely Rhizophora apiculata, Rhizophora stylosa, Ecoecaria agallocha, and Terminalia catappa, where Rhizophora stylosa is a species that dominates.